JURNALIS SEBAGAI FAKTOR DETERMINAN BERITA PADA MEDIA ONLINE HERALD SULSEL - Abu Humaydi Basri; Andi Hasriani; Ratika Nengsi; Muhammad Ishaq Samad; Syamsuriah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the role of journalists in determining news quality and to identify the key factors influencing their performance at the online media outlet Herald Sulsel. The research adopts a qualitative approach using a phenomenological design. Data were collected through in-depth interviews and documentation involving journalists and editorial leaders at Herald Sulsel. The findings indicate that journalists play a central role in the news production process, from selecting story angles and verifying information to structuring and writing news content. Several key determinants influence their role, including educational background, work experience, editorial policies, time constraints, and work environment. The study concludes that news quality in online media is not solely determined by editorial systems but is also heavily dependent on the journalists’ competence, professionalism, and integrity. These results emphasize the importance of continuous professional development and editorial quality control to maintain public trust in the media.